Fit for women: making PPE safe and dignified for women health workers. (8th April 2022) - Dhatt, Roopa; Robalo, Magda; Thompson, Rachel; Okwor, Tochi
Abstract : PPE will not be fit for women unless underlying gender inequities are tackled, say Roopa Dhatt and colleagues